1995
DOI: 10.1007/bf00203117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought stress, abscisic acid, and abscisic acid analogues on the efficacy of diclofop-methyl and tralkoxydim

Abstract: Abstract. The effects of drought stress, abscisic acid (ABA), and four ABA analogues on diclofopmethyl and tralkoxydim efficacy were investigated in oat (Avena sativa). Drought stress conditions (6% soil moisture content) reduced the efficacy of diclofop-methyl at 350 g ha-i, but not at 700 g ha-~. Similarly, tralkoxydim efficacy was reduced by drought stress at 62.5 and 125 g ha-1, but not at 250 g ha-i. ABA (100 ixM), applied as a root drench 2 days before the herbicide, protected oat plants against all rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…This protein belongs to the CYP707A gene family and is associated with controlling ABA levels in late seed maturation through germination [55]. ABA is a phytohormone involved in plant response to abiotic stress and has also been associated with protecting plants from herbicide damage [56, 57]. Devine et al [57] demonstrated that applying exogenous ABA helped protect oats ( Avena sativa L.) against applications of diclofop-methyl or low rates of tralkoxydim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein belongs to the CYP707A gene family and is associated with controlling ABA levels in late seed maturation through germination [55]. ABA is a phytohormone involved in plant response to abiotic stress and has also been associated with protecting plants from herbicide damage [56, 57]. Devine et al [57] demonstrated that applying exogenous ABA helped protect oats ( Avena sativa L.) against applications of diclofop-methyl or low rates of tralkoxydim.…”
Section: Discussionmentioning
confidence: 99%
“…ABA is a phytohormone involved in plant response to abiotic stress and has also been associated with protecting plants from herbicide damage [56, 57]. Devine et al [57] demonstrated that applying exogenous ABA helped protect oats ( Avena sativa L.) against applications of diclofop-methyl or low rates of tralkoxydim. While these transcripts did not respond to herbicide treatment in our analyses, they could represent non-inducible cytochrome P450s that could be differentially expressed between the resistant and susceptible genotypes or may be differentially expressed at timepoints not evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The lower level of precipitation in the week after ICIA 0604 applications at Saskatoon in 1994 and 1997 and the general lack of rainfall throughout the growing season at Scott in 1995 and 1997 may have intensified stress on wild oat plants (Table 2). Devine et al (1995) and Lemerle and Verbeek (1995) showed that ICIA 0604 efficacy was reduced at rates lower than recommended when treatments were applied during periods of drought stress, especially during the period from just before ICIA 0604 application to the end of wheat tiller- ing. Furthermore, rates of absorption and translocation for wild oat and broadleaf weed herbicides can be lower when low humidity and extreme temperatures occur (Nalewaja and Skrzypczak 1986;Nalewaja et al 1990;Smeda and Putnam 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Also, wheat grain yield did not respond to changes in ICIA 0604 rate at all five sites. Drought stress reduced the efficacy of ICIA 0604 applied at rates of 63 and 125 g/ha, but not at 250 g/ha (Devine et al 1995), indicating that the level of wild oat control attained with ICIA 0604 partly depends on environmental conditions.…”
Section: Introductionmentioning
confidence: 91%
“…Water stress increases the levels of endogenous abscisic acid (ABA), which is known to induce gene expression of various antioxidation systems that protect against oxidative stress (Tanaka et al 1990; Ingram and Bartels 1996). Both water stress and pretreatment of susceptible plants with ABA increase the tolerance of susceptible species to DM (Devine et al 1995); perhaps by reducing stomatal aperture and subsequent uptake of DM into the leaves. However, a dramatic shift in the response of membrane potentials to diclofop from a typical susceptible to resistant response was observed in annual ryegrass, wild oat and Alopecurus following water stress or ABA pretreatment (J.…”
Section: Discussionmentioning
confidence: 99%